Evolution of neuronal and glial tau isoforms in chronic traumatic encephalopathy. (2nd July 2020) - Cherry, Jonathan D.; Kim, Soong Ho; Stein, Thor D.; Pothast, Morgan J.; Nicks, Raymond; Meng, Gaoyuan; Huber, Bertrand R.; Mez, Jesse; Alosco, Michael L.; Tripodis, Yorghos; Farrell, Kurt; Alvarez, Victor E.; et al.
Abstract: Chronic traumatic encephalopathy (CTE) is a neurodegenerative tauopathy characterized by accumulation of hyperphosphorylated tau (p‐tau) in perivascular aggregates in neurons and glia at the depths of neocortical sulci and progresses to diffuse neocortical, allocortical and brainstem structures. The strongest risk factor is exposure to repetitive head impacts acquired most commonly through contact sports and military service. Given that CTE can only be definitively diagnosed after death, a better understanding of the cellular and molecular changes in CTE brains may lead to identification of mechanisms that could be used for novel biomarkers, monitoring progression or therapeutic development. Disruption of alternative pre‐mRNA splicing of tau mRNA plays a pathogenic role in tauopathy, with multiple characteristic patterns of isoform accumulation varying among tauopathies. Limited data are available on CTE, particularly at early stages. Using biochemical and histological approaches, we performed a detailed characterization of tau isoform signatures in post‐mortem human brain tissue from individuals with a range of CTE stages (n = 99). In immunoblot analyses, severity was associated with decreased total monomeric tau and increased total oligomeric tau. Immunoblot with isoform‐specific antisera revealed that oligomeric tau with three and four microtubule binding domain repeats (3R and 4R) also increased with CTE severity. Similarly, immunohistochemical studies revealed p‐tau accumulation consisting of both 3R and 4R in perivascular lesions. When the ratio of 4R:3R was analyzed, there was mixed expression throughout CTE stages, although 4R predominated in early CTE stages (I‐II), a 3R shift was observed in later stages (III‐IV). While neurons were found to contain both 3R and 4R, astrocytes only contained 4R. These 4R‐positive cells were exclusively neuronal at early stages. Overall, these findings demonstrate that CTE is a mixed 4R/3R tauopathy. Furthermore, histologic analysis reveals a progressive shift in tau isoforms that correlates with CTE stage and extent of neuronal pathology.